2003
DOI: 10.1093/gerona/58.3.b212
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Morbidity in Laboratory-maintained Rhesus Monkeys and Effects of Long-term Dietary Restriction

Abstract: Mortality and morbidity were examined in 117 laboratory-maintained rhesus monkeys studied over approximately 25 years (8 dietary-restricted [DR] and 109 ad libitum-fed [AL] monkeys). During the study, 49 AL monkeys and 3 DR monkeys died. Compared with the DR monkeys, the AL monkeys had a 2.6-fold increased risk of death. Hyperinsulinemia led to a 3.7-fold increased risk of death (p <.05); concordantly, the risk of death decreased by 7%, per unit increase in insulin sensitivity (M). There was significant organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
153
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(162 citation statements)
references
References 36 publications
7
153
1
Order By: Relevance
“…More broadly, this study reinforces the idea that oocyte aneuploidy and spindle defects are not inevitable consequences of the aging process, thus opening prospects to safely circumvent the negative impact of aging on germline chromosomal segregation during meiosis. And whereas the effects of CR on ovarian function, oocyte dynamics, or germline aneuploidy in primates are currently unknown, recent studies have shown that rhesus monkeys maintained on CR into advanced age exhibit many of the same health benefits as those reported in mouse studies (18,49,50). Thus, it seems reasonable to now add prevention of oocyte aneuploidy and spindle defects, as a means to improve fertility and pregnancy outcomes in women of advanced reproductive age, to the growing list of human health endpoints that might one day become manageable through CR mimetics currently in development (51-55).…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, this study reinforces the idea that oocyte aneuploidy and spindle defects are not inevitable consequences of the aging process, thus opening prospects to safely circumvent the negative impact of aging on germline chromosomal segregation during meiosis. And whereas the effects of CR on ovarian function, oocyte dynamics, or germline aneuploidy in primates are currently unknown, recent studies have shown that rhesus monkeys maintained on CR into advanced age exhibit many of the same health benefits as those reported in mouse studies (18,49,50). Thus, it seems reasonable to now add prevention of oocyte aneuploidy and spindle defects, as a means to improve fertility and pregnancy outcomes in women of advanced reproductive age, to the growing list of human health endpoints that might one day become manageable through CR mimetics currently in development (51-55).…”
Section: Discussionmentioning
confidence: 99%
“…Sirtuins interact with telomeric chromatin and several components of the DNA repair machinery making them potential targets for studies on the mechanisms of oxidative stress in aging (Nakagawa and Guarente, 2011;Michishita et al, 2008). Sirtuins are also energy sensor proteins that respond Experimental Gerontology 79 (2016) [46][47][48][49][50][51][52][53][54] strongly to caloric restriction, a well-recognized intervention to increase life span of lower model organisms and rodents as well as primates Bodkin et al, 2003). Furthermore, sirtuins play a role in the selection of energy source by regulating fatty acid oxidation Nasrin et al, 2010) along with mitochondrial energy metabolism and ATP homeostasis (Ho et al, 2013;Park et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies suggest that reducing calorie intake can also increase the lifespan in nonhuman primates [36,37] . There are two longevity studies (one at the University of Wisconsin, the other at the National Institute on Aging) examining the long-term effects of CR on aging in rhesus monkeys [38] .…”
mentioning
confidence: 99%